Reference equations for handgrip strength: Normative values in young adult and middle-aged subjects - Lopes, Jordão; Grams, Samantha Torres; da Silva, Edy Floriano; de Medeiros, Luana Adriano; de Brito, Christina May Moran; Yamaguti, Wellington Pereira (Clinical nutrition (Edinburgh, Scotland), 2018)
Handgrip strength (HS) has been widely used as a functionality parameter of the upper limbs (UL) and general health. The measurement of HS by dynamometry is a low cost, non-invasive method of simple applicability, widely used in pulmonary rehabilitation and in critical care units. However, there are no reports in the literature of reference equations for the Brazilian population involving young and middle-aged adults. The aim of this study was to establish reference equations to predict normal HS for young and middle-aged adults through demographic and anthropometric data. This is a cross-sectional study with a sample of 80 healthy subjects (40 men and 40 women), aged 20–60 years. Inclusion criteria were: 1) BMI between 18.5 and 30 kg/m2; 2) presence of dominant hand; 3) no cardiac, pulmonary, metabolic, or neurologic diseases; 4) lack of musculoskeletal disorders; 5) no history of fractures or trauma of the UL. Anthropometric measurements of the UL were obtained by a tape (hand length and width, forearm circumference and length). The dominance of hands was defined by the Dutch Handedness Questionnaire. HS measures were obtained by a manual hydraulic dynamometer, according to the recommendations of the American Association of Hand Therapists. Data were analyzed with SPSS for Windows, version 17.0, and treated with descriptive and inferential analysis. Normality was evaluated by Kolmogorov–Smirnov. Pearson or Spearman coefficients and multiple regression analysis were also used. HS was significantly higher for men compared to women, and also higher for the dominant hand (HSD) compared to the non-dominant hand (HSND) (p < 0.05). No significant differences were found for HS between the age groups 20–30, 30–40, 40–50 and 50–60 years (p > 0.05). No correlation was found between HS and age. A weak correlation was found between HS and BMI. A moderate correlation of HS was observed with weight and height. Finally, moderate and high correlations were found between HS and anthropometric variables of UL. The best reference equations with R2, adjusted to 0.71 and 0.70, were respectively: HSDkg = −15.490 + (10.787 × Gender male=1; female=0) + (0.558 × Forearm circumference) + (1.763 × Hand Length); HSNDkg = −9.887 + (12.832 × Gender male=1; female=0) + (2.028 × Hand Length). The variability of HS is largely explained by gender, forearm circumference, and hand length.